Turbo C : sample programs and solutions - Abante, Marmelo V. (Pasig City : Anvil Publishing, 2008)
"C is a general-purpose programming language that features economy of expression, modern control flow and data structures, and a rich set of operations. It is called "system programming language" because it is useful for writing compilers and operating systems." -- Definition of Turbo C
Definition of Turbo C -- Definition of Terms -- The Programming Process -- Sample Programs and Solutions in Turbo C Programming Language -- The ASCII Chart 206 -- IBM PC Extended ASCII Display Characters -- Converting Hex to Decimal -- Converting Hex to Octal.
Keywords: C (COMPUTER PROGRAM LANGUAGE); COMPUTER PROGRAMMING